Providing Compensation to Measur Providing Compensation to Measure the Morale of Employees at PT X: Compensation - June Ardin Telaumbanua (International Journal of Technology and Education Research, 2023)
Providing compensation as a measure of employee enthusiasm at PT X is an absolute right that employees must receive as compensation for their hard work. By providing compensation to employees, they will be more enthusiastic and active in working. The data collection method uses a questionnaire. The data analysis method used is qualitative descriptive analysis. The results show that compensation to employees is given in two forms, namely financial compensation and non-financial compensation. Financial compensation in the form of salary will be given to employees according to the local regional minimum wage and incentives given can be in the form of additional wages and meals for employees who participate in overtime in working on projects at the Company. Providing compensation will also influence employee performance, meaning that providing appropriate compensation will make employees enthusiastic about working.